IDENTIFIKASI GASTROPODA DI SUB DAS ANAK SUNGAI GANDONG DESA KERIK TAKERAN - Mustika Wahyuning Tyas; Joko Widiyanto (UNIVERSITAS PGRI MADIUN, 2015)
The aim of research to determine the diversity and Gastropod that predominate in sub watershed tributary village Gandong Takeran Kerik. Descriptive qualitative research method with type of observational study. Determination and site selection studies using transect sampling method, the size of 1x1 m transect quadrant. Research station at 3 stations with 3 points each station. The data was analyzed after identifying the calculation dominance index and diversity index. Gastropod identification results found 4 genera Thiara, Melanoides, Brotia, and Clea. The highest abundance of gastropods at station II, namely 13.7 ind/m2. Thiara highest dominance index is 0.654, indicating that Thiara mendominansi in sub watershed tributary village Gandong Takeran Kerik. Diversity index of each station 0.617, 0.765, and 0.615, indicating that the diversity of gastropods in sub watershed tributary village Gandong Takeran Kerik is very low. Environmental parameters air temperature 30C - 31C, 28C - 29C water temperature, pH 7 to 7.3, and dissolved oxygen (DO) 5mg /l - 5,4mg /l.